Kajian Kualitas Acara dan Kegiatan Gereja dalam Pertumbuhan Kerohanian Pemuda Berdasarkan Amsal 22:6 di GMAHK Kota Palu - Roring, Miller Bernhard; Hendriks, Alvyn C. (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to analyze the influence of the quality of church events and church activities on the spiritual growth of youth in the Seventh-day Adventist Church of Palu, based on the biblical principle of Proverbs 22:6. A descriptive quantitative approach was used, with a survey method involving 121 youth respondents. The research instruments passed validity and reliability tests. Multiple linear regression analysis showed that both the quality of church events (X1) and church activities (X2) have a positive and significant effect on spiritual growth (Y). The coefficient of determination (R²) was 0.553, indicating that 55.3% of the variance in spiritual growth is explained by the two independent variables. These findings underscore the importance of the church in organizing high-quality and participatory programs to nurture the faith and spiritual character of young people. The application of Proverbs 22:6 serves as the theological foundation for designing effective and contextually relevant youth spiritual development strategies.